2016
DOI: 10.1097/01.sa.0000482341.86369.e7
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Core Temperature Patterns, Transfusion Requirement, and Hospital Duration in Patients Warmed With Forced Air

Abstract: Background-Core temperature patterns in patients warmed with forced-air remain poorly characterized. Also unknown is the extent to which transient and mild intraoperative hypothermia contributes to adverse outcomes in broad populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
63
3
12

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(90 citation statements)
references
References 29 publications
12
63
3
12
Order By: Relevance
“…However, the incidence of perioperative hypothermia in laparoscopic surgery has been found to be comparable to that in patients undergoing open abdominal surgery. 17 In a retrospective study including 58 814 patients, Sun et al 18 recently demonstrated an incidence of hypothermia 3 h after induction of anaesthesia of about 35%. This is lower than our results in the 'no warming' group.…”
Section: Discussionmentioning
confidence: 98%
“…However, the incidence of perioperative hypothermia in laparoscopic surgery has been found to be comparable to that in patients undergoing open abdominal surgery. 17 In a retrospective study including 58 814 patients, Sun et al 18 recently demonstrated an incidence of hypothermia 3 h after induction of anaesthesia of about 35%. This is lower than our results in the 'no warming' group.…”
Section: Discussionmentioning
confidence: 98%
“…It is well documented that mild hypothermia can prolong coagulation times (Sun et al, 2015). More specifically, in the clinical setting, it has been reported that a decrease in core temperature by 3-4°C may cause a decrease in the enzymatic reactions associated with coagulation and thus increase clotting time (Liu and Yenari, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Das Auftreten einer perioperativen Hypothermie erhöht somit die Behandlungskosten [14]. Die intraoperative Inzidenz der perioperativen Hypothermie wird mit bis zu 64 % angegeben und hat eine hohe Relevanz [20].…”
Section: Hintergrundunclassified